Evaluation of eddy current signatures for predicting different heat treatment effects in chromium–vanadium (CrV) spring steel. (April 2017) - Hashmi, Javeria; Khan, Mahmood; Khan, Mushtaq; Jaffery, Syed Husain Imran; Ali, Liaqat; Anwar, Muhammad Nabeel; Subhani, Tayyab
The nondestructive test method (eddy current) was employed to study the effect of different heat treatment cycles (normalizing, annealing, quenching, and tempering) on chromium–vanadium (CrV) spring steel. The calibration of eddy current setup was carried out as per ASTM E566 and frequency optimization for the evaluation of heat treatment was carried out in absolute mode using shielded eddy current testing core probe. The eddy current signatures successfully distinguished the effect of different heat treatments cycles and variation in hardness for CrV samples. Scanning electron microscopy images confirmed the different microstructures as predicted by the eddy current testing.